Changes in Antecedent Soil Moisture Modulate Flood Seasonality in a Changing Climate. Issue 3 (25th February 2020) - Wasko, Conrad; Nathan, Rory; Peel, Murray C.
Abstract: Due to difficulties in identifying a climate change signal in flood magnitude, it has been suggested that shifts in flood timing, that is, the day of annual streamflow maxima, may be detectable. Here, we use high‐quality streamflow, largely free of snowmelt, from 221 catchments across Australia to investigate the influence of shifts in soil moisture and rainfall timing on annual streamflow maxima timing. In tropical areas we find that flood timing is strongly linked to the timing of both rainfall and soil moisture annual maxima. However, in southern Australia flood timing is more correlated with soil moisture maxima than rainfall maxima. The link between flood, soil moisture, and rainfall timing is confounded by event severity: For less extreme events flood timing is more likely to correspond to soil moisture timing, whereas rainfall timing becomes increasingly important as flood severity increases. Using circular regression to investigate nonstationarity, we find that flood timing is shifting to earlier in the year in the tropics and later in the year in the southwest of the continent, consistent with changes in mean and extreme rainfall and shifts in soil moisture timing due to tropical expansion. In southeast Australia, there is evidence that the mechanisms controlling flood seasonality are changing with a reversal of trends post Millennium Drought. Overall, changes in soil moisture timing, compared to changes in rainfall timing, are found to have a greater influence on changes in annual maxima streamflow flood timing. Key Points: Timing of streamflow annual maxima is more closely linked to the timing of antecedent soil moisture maxima than rainfall maxima The more extreme a flood event, the weaker the dependence on antecedent soil moisture relative to rainfall occurrence Using circular regression, streamflow annual maxima timing is found to be nonstationary, consistent with shifts in soil moisture